Fabrication of Polyaniline Thin Film Using Electrodeposition Method as Alcohol Sensor - Ana Yuli Komariyah; Nugrahani Primary Putri (Lembaga Penelitian dan Pengabdian Kepada Masyarakat, LPPM-ITS, 2022)
The use of aliphatic alcohols such as methanol as an alternative renewable fuel in high-density engines can harm both the environment and human health. Polyaniline (PANi), a conductive polymer, has emerged as a solution to this problem because of its benefits as a sensor with relatively high conductivity. In this study, PANi was synthesized using a potentiostat electrodeposition method at a constant potential of -0.4 to +1.0 V at a scan rate of 100 mV/s, resulting in a thin film of PANi on the ITO surface. The formed PANi samples were used to determine the sensitivity level of the sensor to methanol at different concentrations. Morphological results of PANi deposited on the ITO surface were observed using SEM showing the shape of nanoparticles with an interconnected-sponge structure and a porous shape with a diameter of 35.3 nm. The PANI sample can be applied as a sensor material for detecting alcohol vapour in indoor air (at room temperature). The sensing measurement results show that the PANi-based sensor can detect methanol vapour at low concentrations up to 5 ppm. The higher the methanol concentration used, the higher the sensor sensitivity.